Effect of Vamana Karma in Hypothyroidism (International Journal of Ayurveda and Pharma Research, 2025)
Background: Hypothyroidism is one of the metabolic and lifestyle diseases that is having a high prevalence worldwide. The clinical presentation of hypothyroidism includes tiredness, more sensitivity to cold, constipation, dry skin, weight gain, a puffy face, a hoarse voice, coarse hair and skin, muscle weakness, muscle aches, tenderness and stiffness, menstrual cycles that are heavier than usual or irregular, thinning hair, a slowed heart rate (bradycardia), depression, and memory problems. In the Ayurvedic perspective, these symptoms can be correlated to Jatharagni and Dhatwagni abnormalities, as well as Kapha dosha anomalies. Hence, in this clinical experiment, Vamana karma will be used to see how it affects hypothyroidism. Because in Ayurveda, the greatest remedy for vitiated Kapha dosha is Vamana karma. Aim and Objective: To evaluate the effect of Vamana karma in hypothyroidism. Methodology: A single subject was administrated with Deepana Pachana, followed by Snehapana, Swedana, Vamana, and Samsargana krama. Result: There are relevant changes in the thyroid profile.